Community Pharmacists' Awareness of Intimate Partner Violence: An Exploratory Study - Yi Yang, M.D., Ph.D; Erin Holmes, Pharm.D., Ph.D; Donna West-Strum, Ph.D; Marie Barnard, Ph.D; Kristen Alley Swain, Ph.D (University of Minnesota Libraries Publishing, 2013)
Background: Intimate partner violence (IPV) is a serious public health problem, impacting more than 12 million people in the United States each year. The only know effective health care intervention is routine screening for IPV exposure; however, this intervention has been poorly adopted. Expansion of screening efforts to the community pharmacy setting provides an opportunity to have a substantial impact on the health and well-being of pharmacy patients. However, little is known about pharmacists' knowledge, attitudes, and behaviors related to IPV.Objective: The objective of this study was to conduct an exploratory investigation of community pharmacists' current level of knowledge, attitudes, behaviors, and intentions related to IPV and to IPV screening.Methods: A cross-sectional study using an online questionnaire was conducted. Surveys were distributed via email. Descriptive analyses of survey responses were conducted.Results: A total of 144 community pharmacists completed the survey. Results indicated most (67.4%) had no IPV education/training. Participants were significantly more willing to conduct screening with targeted patients compared to all patients. (X2=129.62; df=36; p<0.0001). There was strong agreement with interest in and willingness to participate in continuing education.Conclusions: Most respondents indicated relatively low levels of IPV knowledge and training and very little current IPV screening activity. Continuing education on IPV should be considered for pharmacists to increase knowledge and awareness of IPV.